PENGARUH MOTIVASI KERJA DAN DISIPLIN KERJA TERHADAP KINERJA KARYAWAN PADA PT KARYA MUDA INDAH MEDAN - Bismilawati, Bismilawati (JaManKu: Jurnal Manajemen dan Kewirausahaan, 2025)
Human Resources is basically one of the capital and play an important role in the success of the agency. Good HR management is the key to successful achievement of the agency. To assess the quality of human resources can be measured by the performance of employees. The objective of this study was to determine and influence menganlisis Motivation and Discipline of work the Employee Performance at PT Indah Karya Muda, both partially and simultaneously. The research approach used assoisiatif approach and sampling technique by using saturated sample, as many as 40 people, with data analysis techniques multiple linear regression. The results of this study indicate Motivation effect on Employee Performance at PT Indah Karya Muda, Discipline influential work against Organisasai Citizenship Behavior In Young PT Karya Indah and Motivation and Discipline influential work on Employee Performance at PT Indah Karya Muda. Discipline motivation and work together to have an effect of 80.0% on the Quality of Work, while the remaining 20.0% Employee performance is influenced by other variables not examined in this study